A REVIEW OF THE USES OF ARRAYS IN PROGRAMMING - Anmol Ratan Sanga, Allen; Rathore, Ajeet; Purohit, Abhay; Sharma, Srishti (International Journal of Psychosocial Rehabilitation, 2020)
The accessing, manipulating, and operation of vectors, matrices, and higher-dimensional arrays is done through a compact, powerful, and expressive syntax that has been offered by array programming. The idea of mathematical properties such as the commutative property, reveals that the change in the order of the components or factors does not influence the product of the components. In this paper, we have evaluated that the fundamentals of array conduct an unembellished and influential programming paradigm for sorting, traversing, and analyzing factual data.